Answer:
Option B is the correct answer.
Explanation:
We have equations
4x – 5y = 4 ----------------- equation 1
3x + 2y = –20 ----------------- equation 2
Now we are eliminating y.
equation 1 x 2 gives
8x - 10y = 8 ----------------- equation 3
equation 2 x 5 gives
15 x + 10 y = -100 ----------------- equation 4
Now adding equation 3 and equation 4
8x - 10y + 15 x + 10 y = 8 - 100
23 x = -92
So, y got eliminated
Here we multiplied the first equation by 2 and multiply the second equation by 5 to eliminate y.
Option B is the correct answer.